Comparison of three different conjugation strategies in the construction of herceptin-bearing paclitaxel-loaded nanoparticles. (1st July 2016) - Yu, Kongtong; Zhou, Yulin; Li, Yuhuan; Sun, Xiangshi; Sun, Fengying; Wang, Xinmei; Mu, Hongyan; Li, Jie; Liu, Xiaoyue; Teng, Lesheng; Li, Youxin
Abstract : We developed an improved pre-conjugation strategy, in which herceptin as a ligand was pre-conjugated with DSPE-PEG2000-Mal via chemical cross-linking, followed by conjugation onto the surface of pre-prepared paclitaxel-loaded PLGA/DODMA nanoparticles through hydrophobic interaction and electrostatic attraction for paclitaxel delivery. Abstract : Research on quantitatively controlling the ligand density on the surface of nanocarriers is in the frontier and becomes a technical difficulty for targeted delivery system designing. In this study, we developed an improved pre-conjugation (Imp) strategy, in which herceptin as a ligand was pre-conjugated with DSPE-PEG2000-Mal via chemical cross-linking, followed by conjugation onto the surface of pre-prepared paclitaxel-loaded PLGA/DODMA nanoparticles (PDNs) through hydrophobic interaction and electrostatic attraction for paclitaxel delivery. Compared with the post-conjugation (Pos) strategy, in which the ligand was conjugated onto the nanoparticle surface after the preparation of the nanoparticles, it realized a precise control targeting effect via adjustment of the herceptin density on the surface of the nanoparticles. Within the range of 0–20% of DSPE-PEG2000-herceptin in the blend, it showed a linear relation with the ligand density on the surface of the nanoparticles. The Imp strategy protected the bioactivity of the ligand during the preparation of nanoparticles. At the same time it avoided the waste of an excess amount of herceptin to drive the conjugation reaction in comparison with the post-conjugation (Pos) strategy. The nanoparticles from the Imp strategy showed much better cytotoxicity ( p < 0.001), tumor targeting and cellular uptake efficiency ( p < 0.001) than that of the other strategies in BT474 cells, in which BT474 cells were HER2 receptor over-expression breast cancer cell lines. A significant reduction in cellular uptake of the nanoparticles from the Imp strategy was observed in the presence of sucrose and cytochalasin D, indicating that clathrin-mediated and caveolae-dependent endocytosis was as a primary mechanism of cellular entry for these antibody-modified nanoparticles.